2015
DOI: 10.1556/038.50.2015.1.7
|View full text |Cite
|
Sign up to set email alerts
|

New data to the mite fauna of Hungarian bamboo plantations

Abstract: Five different bamboo plantations were investigated on the basis of the leaf litter inhabiting mites. 11 Mesostigmata and 10 Oribatida are listed from the leaf litters, of which three species, e.g. Vulgarogamasus kraepelini (Berlese, 1905), Nothrus parvus Sitnikova, 1975, Metabelba paravulverosa Moritz, 1966 are new to the Hungarian fauna.Keywords: Acari, Mesostigmata, Oribatida, bamboo leaf litter, new occurrences, Hungary.Acarological researches have a long tradition in Hungary (Horváth et al., 2010), but mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Comparing the present research with data obtained from other studies in Europe on the Mesostigmata of urban soils, the number of species identified in Bucharest is comparable with totals obtained in Latvia and Poland, in such different habitats as roadsides, greenery, parks and urban forests (25–51 species), but is higher than that for mite communities in a botanical garden in Hungary (12 species) 40 , 42 , 45 , 47 . However, the number of recorded species is lower than suburban and urban green areas from Poland (62–68 species), urban grasslands from Latvia or cemeteries and botanical garden in Slovakia (123 species, in three years of study) 34 , 35 , 38 , 39 , 43 .…”
Section: Discussionsupporting
confidence: 87%
“…Comparing the present research with data obtained from other studies in Europe on the Mesostigmata of urban soils, the number of species identified in Bucharest is comparable with totals obtained in Latvia and Poland, in such different habitats as roadsides, greenery, parks and urban forests (25–51 species), but is higher than that for mite communities in a botanical garden in Hungary (12 species) 40 , 42 , 45 , 47 . However, the number of recorded species is lower than suburban and urban green areas from Poland (62–68 species), urban grasslands from Latvia or cemeteries and botanical garden in Slovakia (123 species, in three years of study) 34 , 35 , 38 , 39 , 43 .…”
Section: Discussionsupporting
confidence: 87%
“…The agricultural soils usually are poor in the organic material; therefore the species number and the frequency of the oribatid species are lower than mesostigmatans. The Rhysotritia ardua species was collected in higher number in the studied agroecosystems, this species usually occurs in other unstable habitats and other plantations (Kontschán et al, 2015) as well.…”
Section: Discussionmentioning
confidence: 99%
“…Our first steps were the investigation of the Hungarian bamboo plantations in which we found numerous mites species as well (Kontschán et al, 2014(Kontschán et al, , 2015. This study contains our new results of the soil dwelling mites of several different Hungarian agroecosystems.…”
mentioning
confidence: 91%
“…However, information about their occurrence in Hungary is insufficient, although numerous records were presented over the past 20 years (e.g. Ács and Kontschán 2014, Kontschán 2005, 2006, 2015, Kontschán et al 2014, 2015a, 2015b, 2016, Salmane and Kontschán 2005, 2006). Only a few beetle-associated macrochelids have been mentioned (Kontschán 2006) from Hungary, while macrochelid mites associated with centoniin beetles are rarely collected.…”
Section: Introductionmentioning
confidence: 99%